Awareness of Consumer: Consumer Purchase Intention and Purchase Behavior towards Halal Products - Devi Yulia Rahmi; Fikri Alwi; Ratni Prima Lita; Fatma Poni Mardiah (Journal of Management and Entrepreneurship Research, 2025)
Objective: The study aims to examine the effect of halal awareness, halal logo, religiosity, and price on consumers' intention to buy food products with a halal logo. This study also examines the effect of purchase intention on consumer purchase behaviour of food products with the halal logo Research Design & Methods: This study uses a quantitative method with 200 respondents who consume food products with the halal logo in West Sumatra. Data were analyzed using the PLS-SEM (Partial Least Square-Structural Equational Modeling) method. Findings: The results of the study show that the halal logo, religiosity, and price are significant for purchase intention. No significant effect was found on halal awareness and attitude towards purchase intention. Moreover, the study's results show that purchase intention significantly affects purchase behaviour. Implications and Recommendations: This research implies that consumers of food products labelled halal consider the halal logo on a product before consuming it, so food producers must try to sell products that have a halal logo Contribution & Value Added: This study addresses the existing literature by modifying the research model regarding the purchase behaviour of halal products. In practical, companies in the halal food industry should focus on maintaining and enhancing product quality, obtaining halal certification, and establishing a trusted halal label to foster consumer purchase intention and behavior.